Phalangeal Reaming and Irrigation for Combined Proximal and Distal Phalangeal Osteomyelitis of the Thumb - Austin Franklin, MD; Angel Valencia, MD; Dang-Huy Do, MD; Ann Golden, MD; Daniel Koehler, MD (Journal of Hand Surgery Global Online)
Acute and chronic osteomyelitis of the phalanges may lead to digital amputation because of the difficulty of adequately debriding infected tissue, while concurrently maintaining the delicate function of the digit. In our patient with osteomyelitis of the proximal and distal thumb phalanges as well as the adjoining interphalangeal joint, we used a reamer-irrigator-aspiration system, commonly used in nonunion and long bone osteomyelitis, to effectively ream the intramedullary canals of the phalanges. This allowed for adequate debridement and irrigation of our patient’s deep space infection using a minimally invasive approach, while avoiding more extensive debridement or amputation. After completion of 6 weeks of intravenous antibiotics, this patient successfully cleared the osteomyelitis while maintaining the function of her thumb.